Fecal microbiota transplantation from HUC-MSC-treated mice alleviates acute lung injury in mice through anti-inflammation and gut microbiota modulation - Hua, Feng; Cui, Enhai; Lv, Lu; Wang, Bin; Li, Liqin; Lu, Huadong; Chen, Na; Chen, Wenyan (Frontiers in Microbiology, 2023)
Acute lung injury (ALI) is a severe respiratory tract disorder facilitated by dysregulated inflammation, oxidative stress and intestinal ecosystem. Fecal microbiota transplantation (FMT) is a rapid method for gut microbiota (GM) reconstruction. Furthermore, our previous studies have confirmed that human umbilical cord mesenchymal stromal cells (HUC-MSCs) can alleviate ALI by improving GM composition. Therefore, we aimed to explore the efficacy and mechanism of FMT from HUC-MSCs-treated mice on ALI. Briefly, fresh feces from HUC-MSCs-treated mice were collected for FMT, and the mice were randomly assigned into NC, FMT, LPS, ABX-LPS and ABX-LPS-FMT groups (n=12/group). Subsequently, the mice were administrated with antibiotic mixtures to deplete GM, and given lipopolysaccharide and FMT to induce ALI and rebuild GM. Our results revealed that FMT obviously improved the pathological damage of lung and ileum, recovered the immune system of peripheral blood, decreased the cell apoptosis of lung, inhibited inflammation and oxidative stress in bronchoalveolar lavage fluid (BALF), serum, lung and ileum tissues. Moreover, FMT also elevated ZO-1, claudin-1, and occludin protein expressions, activating Nrf2/HO-1 pathway but hindering TLR4/NF-κB pathway. Of note, the relative abundances of Bacteroides, Christensenella, Coprococcus and Roseburia were decreased, while the relative abundances of Xenorhabdus, Sutterella and Acinetobacter were increased in the ABX-LPS-FMT group. In conclusion, FMT from HUC-MSCs-treated mice may alleviate ALI by inhibiting inflammation and reconstructing GM, additionally, we also found that the TLR4/NF-KB and Nrf2/HO-1 pathways may involve in the improvement of FMT on ALI, which offers novel insights for the functions and mechanisms of FMT from HUC-MSCs-treated mice on ALI.